What are the factors predictive of postoperative complications in patients with colorectal cancer undergoing stenting as a bridge to surgery?. Issue 6 (31st January 2022) - Adachi, Yuki; Tokunaga, Ryuma; Matsumoto, Katsutaka; Nakao, Yosuke; Itoyama, Rumi; Kuramoto, Kazutoshi; Karashima, Ryuichi; Nitta, Hidetoshi; Tomiyasu, Shinjiro; Baba, Hideo; Takamori, Hiroshi
Abstract: Objective: Using a self‐expanding metal stent as a bridge to surgery (BTS) is considered a reasonable strategy for patients with acute malignant large bowel obstruction. Since postoperative complications have a negative impact on patient survival, we aim to clarify the predictors of complications in patients undergoing BTS using a self‐expanding metal stent. Methods: We conducted a retrospective review of 61 patients with colorectal cancer (CRC) who underwent stenting as a BTS at our institution. We analyzed the association of postoperative complications with clinicopathologic, surgical, and patient factors, and with the prestenting or preoperative laboratory data. Results: Both postoperative complications in general and severe complications were significantly associated with a longer stenotic‐section length ( p = 0.007 and p = 0.003), lower preoperative hemoglobin levels ( p < 0.001 and p = 0.081), and lower prestenting hemoglobin levels ( p = 0.006 and p = 0.042). Multivariate logistic regression analysis showed that lower prestenting (<13.0 g/dl) and preoperative (<11.5 g/dl) hemoglobin levels were independent predictive factors for postoperative complications (odds ratio [OR]: 4.15; 95% confidence interval [CI]: 1.07–18.90; p = 0.040; and OR: 4.93; 95% CI: 1.35–20.28; p = 0.016). A stenotic‐section length of 5.0 cm or greater was predictive of severe complications (OR: 25.67; 95% CI: 1.95–1185.00; p = 0.011). Conclusions: Our data suggest that lower hemoglobin levels before stenting and a longer length of the stenotic section of bowel might predict postoperative complications in patients with CRC undergoing BTS for obstruction.